METHODS OF PHYSICAL MODELING OF HYDRODYNAMIC PROCESSES AT CASTING OF ALLOYS - V. Ju. Stetsenko (Литьë и металлургия)
The method of physical modeling of hydrodynamic processes of alloys molding is developed. It is shown that as a liquid it is necessary to use water and diethyl ether at molding of steel, silumins, tin-base bronzes and waterglycerine solutions.